(untitled) (KULT_online, 2017)
The critique of normative identity constructions, gender binary, and heterosexuality is far away from being an integral part of academic research. The edited volume Queer as... – Kritische Heteronormativitätsforschung aus interdisziplinärer Perspektive attempts to partly close this pertinent research gap. In order to open the reader’s eyes to a heteronormative, critical way of thinking about academia, art, pedagogy, law, and everyday life, scientists of different disciplinary backgrounds convincingly explore the relations of queer knowledge and practices in everyday life and science.